A Critical Examination of the Position of Mr. Darwin's Work, "On the Origin of Species," in Relation to the Complete Theory of the Causes of the Phenomena of Organic Nature : Lecture VI. (of VI.), "Lectures to Working Men", at the Museum of Practical Geology, 1863, on Darwin's Work: "Origin of Species" - Huxley, Thomas Henry, 1825-1895 (Salt Lake City, UT : Project Gutenberg, 2001)
"A Critical Examination of the Position of Mr. Darwin's Work, 'On the Origin of Species,' in Relation to the Complete Theory of the Causes of the Phenomena of Organic Nature" by Thomas H. Huxley is a scientific publication written during the late 19th century. This work critically assesses Charles Darwin's theories on evolution, particularly the arguments presented in "On the Origin of Species." The book seeks to clarify, defend, and evaluate Darwin's contributions to biology, particularly in the context of organic evolution and species development. In this examination, Huxley provides an in-depth analysis of Darwin's theories, highlighting both their strengths and limitations. He distinguishes between the questions of how organic beings originate and how they modify and perpetuate over time, arguing that while Darwin's work effectively addresses the latter, it does not tackle the former. Huxley critiques various objections raised against Darwin's hypotheses, particularly regarding the issue of hybrid sterility and the persistence of certain species types. He emphasizes the importance of evidence in supporting Darwin's claims and ultimately concludes that Darwin's work represents a significant advancement in biological science, expecting its principles to guide future exploration and understanding in this field. (This is an automatically generated summary.)
Release date is 2001-11-01
Produced by Amy E. Zelmer, and David Widger
Keywords: Evolution (Biology); Darwin, Charles, 1809-1882. On the origin of species